2023
DOI: 10.1111/eva.13540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthropogenic stress on hosts and their microbiomes: Treated wastewater alters performance and gut microbiome of a key detritivore (Asellus aquaticus)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 178 publications
(251 reference statements)
0
0
0
Order By: Relevance
“…The largest contributors to the observed differences between the control and MP treatment included, among many others, genera Rhizobium , Legionella , Flavobacterium , Corynebacterium and Streptomyces (Figure S5). These are typical environmental microbes with diverse metabolic repertoires, which were also recently retrieved in a survey of the A. aquaticus microbiome originating from the same population (Lafuente et al, 2023). The effect of MPs was observed not only in terms of bacterial community structure, but also bacterial diversity.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The largest contributors to the observed differences between the control and MP treatment included, among many others, genera Rhizobium , Legionella , Flavobacterium , Corynebacterium and Streptomyces (Figure S5). These are typical environmental microbes with diverse metabolic repertoires, which were also recently retrieved in a survey of the A. aquaticus microbiome originating from the same population (Lafuente et al, 2023). The effect of MPs was observed not only in terms of bacterial community structure, but also bacterial diversity.…”
Section: Discussionmentioning
confidence: 97%
“…A. aquaticus has been described as a species with a great tolerance to environmental pollution, although the mechanisms by which it bioaccumulates and metabolises these toxins are not fully understood (O'Callaghan et al, 2019). There are documented cases with no detectable effects of organic pollution on survival and growth (Bundschuh et al, 2012; Ieromina et al, 2014), while other studies have demonstrated a significant reduction in A. aquaticus abundance (Bayona et al, 2015), changes in behaviour (De Lange et al, 2006) or changes in growth rate (Gardeström et al, 2016; Lafuente et al, 2023). The MP mixture of 17 different organic compounds, which mimicked the conditions at impacted sites in Swiss streams (Stamm et al, 2016), has been also applied to other freshwater animals, but it generally showed mixed results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations